2002
DOI: 10.1073/pnas.192174199
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent life-history traits promote catastrophic collapses of top predators

Abstract: Catastrophic population collapses such as observed in many exploited fish populations have been argued to result from depensatory growth mechanisms (i.e., reduced reproductive success at low population densities, also known as Allee effect). Empirical support for depensation from population-level data is, however, hard to obtain and inconclusive. Using a size-structured, individualbased model we show that catastrophic population collapses may nonetheless be an intrinsic property of many communities, because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
240
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(242 citation statements)
references
References 26 publications
2
240
0
Order By: Relevance
“…Clearly identifying the consequences of this positive feedback allows for the development of management actions that at first sight seem counter-intuitive. For example, De Roos and Persson (2002) suggested that, if indeed the change in prey population size distribution after a predator collapse prohibits recovery of the predator, thinning the prey population might be an effective strategy to foster recovery. Modeling studies suggested that such a counter-intuitive approach might be more successful than release or stocking of predators (van Kooten et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly identifying the consequences of this positive feedback allows for the development of management actions that at first sight seem counter-intuitive. For example, De Roos and Persson (2002) suggested that, if indeed the change in prey population size distribution after a predator collapse prohibits recovery of the predator, thinning the prey population might be an effective strategy to foster recovery. Modeling studies suggested that such a counter-intuitive approach might be more successful than release or stocking of predators (van Kooten et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism, referred to as an emergent Allee effect (De Roos and Persson, 2002;see Fig. 1 for a schematic representation), has been shown to occur in predatorprey-resource systems when predators forage exploitatively on selective size ranges of prey only.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed analysis by de Roos, Persson and Thieme (2003) shows that the essence of the matter is that in the absence of predators the consumer population is regulated mainly by the rate at which individuals pass through a certain size range, with the predators specialising on a different size range. As noted by de Roos and Persson (2002), a mechanism of this sort may well explain the failure of the Northwest Atlantic cod to recover after its collapse from overfishing: After the cod collapsed, the abundance of their main food, capelin, increased, but capelin growth rates decreased and adults became significantly smaller. (See Scheffer et al (2001) for a general survey on catastrophic collapses.…”
Section: Ecological Motivationmentioning
confidence: 94%
“…In this section, we describe work on a food chain model developed by de Roos and Persson (2002). The model recognizes three trophic levels: a resource, a size structured consumer population that feeds on the resource, and an unstructured predator population that feeds on the small consumers.…”
Section: Integrating Information From Ibm and Pspm Modeling: A Case Smentioning
confidence: 99%
“…Thus, in section 2, we describe features that can be understood by comparison of representations of populations that do, and do not, contain discrete individuals. In section 3, we compare/contrast the properties of a three-trophiclevel model (resource-consumer-predator) for which previous analysis of a PSPM demonstrated the possibility of bistability, hysteresis and population cycles (De Roos and Persson, 2002) with an analogous IBM that demonstrates how different forms of stochasticity influence qualitative outcome including invasion, persistence or extinction of the predator. The case study also demonstrates the value of "dialog" between the two approaches.…”
Section: Introductionmentioning
confidence: 99%